Industry in Libya between administration and strategic management - المنصوري , عبد الجليل أدم (Dirasat in Economics and Business, 2005)
There is no doubt that the main difference between developed and less developed countries comes from the management gap between the two categories. Hence, it could be said that understanding of management is highly important in determining the status of the state of being developed or coming short of that.